Museum A. Vanderhaeghen. - Museum A. Vanderhaeghen, Gent (Gent : Museum A. Vanderhaeghen, 1959)
Landuyt, Octave ; Burssens, Jan ; Foncke, Richard ; Mees, Jozef-Maurits ; Raveel, Roger ; Van Gysegem, Paul
Museum A. Vanderhaeghen, Gent, 14.2. - 1.3.1959
boek